Faktor Yang Mempengaruhi Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Tenaga Kesehatan : Literatur Review - Kurnia Ningrum; Risti Graharti; TA Larasati (Medula, 2026)
Abstract The use of Personal Protective Equipment (PPE) is a key component of infection prevention and control in healthcare facilities. Compliance among healthcare workers determines the effectiveness of protection against biological, chemical, and physical hazards in the workplace. However, PPE compliance remains a challenge in many healthcare settings. This literature review aims to identify factors influencing PPE compliance among healthcare workers based on recent studies. The review was conducted using Google Scholar, PubMed, and ScienceDirect databases with the keywords “personal protective equipment,” “compliance,” and “healthcare workers.” Articles published between 2015 and 2025 were included. Of the 62 articles identified, 13 met the inclusion criteria and were analyzed in depth. The analysis focused on synthesizing findings related to individual, organizational, and work environment factors affecting PPE compliance. The results show that individual factors such as knowledge, attitude, risk perception, and work experience significantly influence compliance behavior. Organizational factors, including PPE availability, institutional policies, supervision, safety culture, and continuous training, also play an important role in shaping compliance. In addition, work environment factors such as workload, comfort of PPE, and physical conditions of care areas contribute to compliance levels. Understanding these factors is essential for improving patient and healthcare worker safety through comprehensive intervention strategies. Improving education, strengthening institutional policies, and ensuring adequate PPE supply systems are expected to enhance compliance. In Indonesia, integrated studies examining factors influencing PPE compliance remain limited, highlighting the need for further research to support policy development and occupational safety practices for healthcare workers.